ANALISIS ZAT GIZI MAKRO DAN DAYA TERIMA NUGGET PISANG KEPOK (Musa paradisiaca formatypica) UBI UNGU (Ipomoea batatas L. Poir) - Asmulyati Saleh; Maria F.Vinsensia D.P Kewa Niron; Agustina Setia (Poltekkes Kemenkes Kupang, 2022)
Various efforts to support the national food security program are carried out to maximize the production and consumption of local food sources of non-rice and non-wheat carbohydrates, which are the government's priorities, especially in the field of diversification. The current effort to diversify food consumption is not only to provide diverse and nutritious food, but has begun to develop to the consideration of health benefits. One of the abundant agricultural ingredients is banana kepok. This study aims to determine the nutritional and organoleptic values ​​of kepok banana flour and purple sweet potato nuggets. This type of research is an experiment using a completely randomized design (CRD) with 4 levels of treatment, namely A0, A1, A2, and A3. Treatment A0 used the standard recipe for nuggets and 3 (three) other treatments were substitution of banana kepok flour and purple sweet potato flour with the ratio of banana kepok flour: purple sweet potato flour: wheat flour was A1 40%:30%:30%, A2 50%: 25%:25%, and A3 60%:20%:20%. The nugget formula was then tested for macronutrient value and acceptability assessment (assessment of color, aroma, texture, and taste). The results obtained showed that the organoleptic characteristics of the kepok banana flour substituted purple sweet potato nuggets include taste, texture, aroma and color in both treatments A0, A1, A2 and A3 ranging from like to very like. And the most preferred nutritional value of kepok banana flour nuggets substituted with purple sweet potato flour is treatment (A1) with macronutrient content of gross carbohydrates 86.82%, protein 9.36% and fat 3.55%